Effect of jaw clenching on head acceleration during a predictable load impact. (15th September 2021) - Sako, Kazuki; Tanaka, Yuto; Tomita, Yosuke; Yoshida, Tsuyoshi; Ono, Yoshiaki; Kashiwagi, Kosuke
Abstract: Background: Jaw clenching is considered to reduce head acceleration while receiving a strong impact on the body during sport activities. Objective: The present study aimed to clarify the effect of jaw clenching on reduction of head acceleration during a predictable load impact to the body. Methods: Seven healthy participants were exposed to a predictable load impact with and without jaw clenching. We recorded the electromyographic activity of the masseter (MA) and digastricus (DIG) muscles, occlusal pressure and head acceleration throughout the experiment. Results: When participants were not instructed to clench their jaws, they naturally positioned their jaws without occlusal contact at the time of pendulum impact by co‐contracting the jaw opener and closer muscles. When participants were instructed to clench their jaws, neither the activity of the jaw opener muscle nor the head acceleration differed at the time of pendulum impact when compared with when participants were not instructed to clench their jaws. Conclusions: A slightly distanced jaw position (co‐contracting the jaw opener and closer muscles without occlusal contact) might serve inherently safety for reduction of head acceleration during predictable body impact, while jaw clenching does not contribute to reduction of head acceleration in response to pendulum impact more than the distanced jaw position does. Notably, DIG activation to minimise the head acceleration in response to pendulum impact was similar in clenching and no clenching positions. This suggests that DIG may play a crucial role in the reduction of head acceleration, regardless of MA muscle activity. Abstract : Jaw clenching does not contribute to reduction of head acceleration in response to a pendulum impact more than the distanced jaw position does.